Origin and flow-mediated remodeling of the murine and human extraembryonic circulation systems - Van Schoor, Kristof; Bruet, Emmanuel; Jones, Elizabeth Anne Vincent; Migeotte, Isabelle (Frontiers in Physiology, 2024)
The transduction of mechanical stimuli produced by blood flow is an important regulator of vascular development. The vitelline and umbilico-placental circulations are extraembryonic vascular systems that are required for proper embryonic development in mammalian embryos. The morphogenesis of the extraembryonic vasculature and the cardiovascular system of the embryo are hemodynamically and molecularly connected. Here we provide an overview of the establishment of the murine and human vitelline and umbilico-placental vascular systems and how blood flow influences various steps in their development. A deeper comprehension of extraembryonic vessel development may aid the establishment of stem-cell based embryo models and provide novel insights to understanding pregnancy complications related to the umbilical cord and placenta.